Does Brownfield sites impact on nearby property prices? / Nur Zafira Zihannudin and Nurul Hana Adi Maimun - Zihannudin, Nur Zafira; Adi Maimun, Nurul Hana (2021)
Brownfield site is one of the main challenges that Malaysia has to face as a result of financial, administrative and policy problems. Negative environmental and social impacts of Brownfield sites jeopardize the health and well-being of residents causing nearby areas to be less desirable for occupation and investment resulting in price discounts. Hence, this research aims to critically review the magnitude of the impact of Brownfield site on property prices. An overview on previous studies has shown that property prices are significantly influenced by proximity to Brownfield sites. This indicates that the proximity to Brownfield site is accounted for when making property purchase decisions.